Environmental Filtering Drives Widespread Trait Convergence in Marine Demersal Ray‐Finned Fishes - Liam MacNeil; Matthew McLean; Derek P. Tittensor; Till Bayer; Thorsten B. H. Reusch; Marco Scotti (Global Ecology and Biogeography, 2025)
Aim Understanding the processes that shape the distribution of biodiversity in the oceans is central for predicting and conserving ecosystems under global change. Although a vast literature exists on drivers of species diversity, the geographical patterns and drivers of ecosystem functioning, and in particular the traits that shape this functioning, remain relatively unexplored. We address this gap by testing the effects of environment, fishing pressure and evolutionary history on fish trait compositions across continental shelf seas using scientific trawl surveys. Location Northern Hemisphere shelf seas. Time Period 1999–2021. Major Taxa Studied Marine demersal ray‐finned fishes. Methods Here, we aggregate trawl and trait information (body size, habitat, reproduction, trophic ecology and growth) for 1164 demersal ray‐finned fishes on continental shelf seas throughout the Northern Hemisphere to test the relative importance of environmental, evolutionary and anthropogenic drivers in shaping trait compositions. These patterns are tested across three different spatial scales (100 km 2 to marine Ecoregions) using linear and non‐linear models. We also compare trait compositions to expectations under null and neutral models. Results Trait compositions throughout shelf seas are always positively related to environmental conditions but appear strongly associated with evolutionary history on the northeast Pacific shelves. Although fishing can alter individual traits and deplete populations, it shows no explanatory power in describing trait compositions. The majority (81%) of trait compositions are more similar than expected under neutral drift. Main Conclusions We find that environmental filtering has strongly shaped the functional convergence of fish communities while, in contrast to expectations, phylogenetic conservatism across evolutionary lineages appears uniquely strong in the Pacific Ocean but less important in the Atlantic. The widespread role of environmental conditions in shaping fish traits highlights the potential sensitivity of community functioning to environmental and climate change and sheds new light on the potential for trait‐based conservation strategies.

Declines in sightings and changing visitation patterns of reef manta rays at an important aggregation site in Mozambique - Nakia Cullain; Yara Tibiriçá; Stephanie K. Venables; Christoph A. Rohner; Derek P. Tittensor; Heike K. Lotze (Environmental Biology of Fishes, 2025)

Climate change implications in the suitable habitat of olive ridley turtle Lepidochelys olivacea in the Eastern Tropical Pacific - Elka García-Rada; Aura Buenfil-Ávila; Christine Figgener; Héctor M. Guzmán; Pamela T. Plotkin; Gabriel Reygondeau; Carlos Robalino-Mejía; Derek P. Tittensor; Héctor Villalobos; César Peñaherrera-Palma (Marine Environmental Research, 2025)

Sampling Simulation in a Virtual Ocean Reveals Strong Sampling Effect in Marine Diversity Patterns - André Menegotto; Derek P. Tittensor; Robert K. Colwell; Thiago F. Rangel (Global Ecology and Biogeography, 2025)
Aim Undersampling and other sources of sampling bias pose significant issues in marine macroecology, particularly when shaping conservation and management decisions. Yet, determining the extent to which such biases impact our understanding of marine diversity remains elusive. Here, utilising empirical data on sampling efforts, we sampled from virtually established species distributions to evaluate how deep is the influence of sampling bias on estimations of the latitudinal gradient in marine diversity. Location Atlantic Ocean. Time Period Present. Taxa Studied Ophiuroidea. Methods We developed a computer simulation that implements two null models of species distribution (the geometric constraints and the area model) in a two‐dimensional domain, replicates the latitudinal distribution of historical sampling efforts and then quantifies diversity metrics (observed and estimated species richness) and sample completeness for each grid cell and latitudinal band. Results We found consistent patterns of observed species richness across models, noting peaks at midlatitudes regardless of whether the true richness was unimodal or flat. Dips in equatorial diversity persisted even after using different methods of species richness estimation. Additional simulations showed that estimators' accuracy improved with increased sampling efforts, but only when samples were randomly distributed. Spatially aggregated samples inflate completeness without necessarily enhancing estimators' accuracy. Main Conclusions This finding emphasises the imperative of bolstering sampling efforts at tropical latitudes and deploying robust statistical techniques to mitigate undersampling effects. Meanwhile, we suggest considering sampling bias as an alternative null hypothesis for recorded marine diversity patterns.

Status, challenges and pathways to the sustainable use of wild species - Jean-Marc Fromentin; Marla R. Emery; John Donaldson; Ganesan Balachander; Elizabeth S. Barron; Ram P. Chaudhary; Marie-Claire Danner; Maria A. Gasalla; Agnès Hallosserie; Marwa Halmy; Christina Hicks; Daniel Kieling; et al. (Global Environmental Change, 2023)

The status of climate change adaptation in fisheries management: Policy, legislation and implementation - Andrea Bryndum‐Buchholz; Derek P. Tittensor; Heike K. Lotze (Fish and Fisheries, 2021)
Climate change is altering ecosystems and fisheries throughout the world's oceans, demanding climate‐adaptive governance for conserving and managing living marine resources. While in some regions fisheries management systems address wider ecosystem dynamics within management frameworks and decision‐making, which may facilitate resilience to climate change, there remains a shortfall in terms of directly incorporating climate change adaptation into fisheries management legislation and implementation. This review assesses the current state of implementation of climate change adaptation into fisheries management policies and legislation across 11 national case studies, based on government documents and the primary literature. The overarching goal is to understand the key elements and gaps in existing fisheries management policies and legislation in the context of climate change. Given recent reforms of fisheries management policies and/or legislation across the nations examined, political recognition of the need to address climate change adaptation in fisheries management appears to be increasing; albeit formal mandates of climate‐adaptation objectives in fisheries management are largely missing. Based on our review, recommendations for achieving climate‐adaptive fisheries management regimes are developed. Overall, this study will help to inform and broaden the scope of management approaches and tools to accelerate the move towards adaptive fisheries management that accounts for climate change impacts on fish stocks, fisheries and the societies that depend upon them.

Advancing Global Ecological Modeling Capabilities to Simulate Future Trajectories of Change in Marine Ecosystems - Marta Coll; Jeroen Steenbeek; Maria Grazia Pennino; Joe Buszowski; Kristin Kaschner; Heike K. Lotze; Yannick Rousseau; Derek P. Tittensor; Carl Walters; Reg A. Watson; Villy Christensen (Frontiers in Marine Science, 2020)

Time Machine Biology: Cross-Timescale Integration of Ecology, Evolution, and Oceanography - Moriaki Yasuhara; Huai-Hsuan Huang; Pincelli Hull; Marina Rillo; Fabien Condamine; Derek Tittensor; Michal Kučera; Mark Costello; Seth Finnegan; Aaron O’Dea; Yuanyuan Hong; Timothy Bonebrake; et al. (Oceanography, 2020)

Incorporating climate change adaptation into marine protected area planning - Kristen L. Wilson; Derek P. Tittensor; Boris Worm; Heike K. Lotze (Global Change Biology, 2020)
Climate change is increasingly impacting marine protected areas (MPAs) and MPA networks, yet adaptation strategies are rarely incorporated into MPA design and management plans according to the primary scientific literature. Here we review the state of knowledge for adapting existing and future MPAs to climate change and synthesize case studies ( n = 27) of how marine conservation planning can respond to shifting environmental conditions. First, we derive a generalized conservation planning framework based on five published frameworks that incorporate climate change adaptation to inform MPA design. We then summarize examples from the scientific literature to assess how conservation goals were defined, vulnerability assessments performed and adaptation strategies incorporated into the design and management of existing or new MPAs. Our analysis revealed that 82% of real‐world examples of climate change adaptation in MPA planning derive from tropical reefs, highlighting the need for research in other ecosystems and habitat types. We found contrasting recommendations for adaptation strategies at the planning stage, either focusing only on climate refugia, or aiming for representative protection of areas encompassing the full range of expected climate change impacts. Recommendations for MPA management were more unified and focused on adaptative management approaches. Lastly, we evaluate common barriers to adopting climate change adaptation strategies based on reviewing studies which conducted interviews with MPA managers and other conservation practitioners. This highlights a lack of scientific studies evaluating different adaptation strategies and shortcomings in current governance structures as two major barriers, and we discuss how these could be overcome. Our review provides a comprehensive synthesis of planning frameworks, case studies, adaptation strategies and management actions which can inform a more coordinated global effort to adapt existing and future MPA networks to continued climate change.

Twenty‐first‐century climate change impacts on marine animal biomass and ecosystem structure across ocean basins - Andrea Bryndum‐Buchholz; Derek P. Tittensor; Julia L. Blanchard; William W. L. Cheung; Marta Coll; Eric D. Galbraith; Simon Jennings; Olivier Maury; Heike K. Lotze (Global Change Biology, 2019)
Climate change effects on marine ecosystems include impacts on primary production, ocean temperature, species distributions, and abundance at local to global scales. These changes will significantly alter marine ecosystem structure and function with associated socio‐economic impacts on ecosystem services, marine fisheries, and fishery‐dependent societies. Yet how these changes may play out among ocean basins over the 21st century remains unclear, with most projections coming from single ecosystem models that do not adequately capture the range of model uncertainty. We address this by using six marine ecosystem models within the Fisheries and Marine Ecosystem Model Intercomparison Project (Fish‐MIP) to analyze responses of marine animal biomass in all major ocean basins to contrasting climate change scenarios. Under a high emissions scenario (RCP8.5), total marine animal biomass declined by an ensemble mean of 15%–30% (±12%–17%) in the North and South Atlantic and Pacific, and the Indian Ocean by 2100, whereas polar ocean basins experienced a 20%–80% (±35%–200%) increase. Uncertainty and model disagreement were greatest in the Arctic and smallest in the South Pacific Ocean. Projected changes were reduced under a low (RCP2.6) emissions scenario. Under RCP2.6 and RCP8.5, biomass projections were highly correlated with changes in net primary production and negatively correlated with projected sea surface temperature increases across all ocean basins except the polar oceans. Ecosystem structure was projected to shift as animal biomass concentrated in different size‐classes across ocean basins and emissions scenarios. We highlight that climate change mitigation measures could moderate the impacts on marine animal biomass by reducing biomass declines in the Pacific, Atlantic, and Indian Ocean basins. The range of individual model projections emphasizes the importance of using an ensemble approach in assessing uncertainty of future change.

A neutral‐metabolic theory of latitudinal biodiversity - Derek P. Tittensor; Boris Worm (Global Ecology and Biogeography, 2016)
Aim Latitudinal gradients of species richness represent Earth's first‐order biodiversity pattern. Most species groups display a near‐monotonic decline in richness from the equator to the poles, yet there exists little mechanistic theory to derive such patterns from first principles. Here we integrate two key advances – neutral theory and the metabolic theory of ecology – to reconstruct global species richness gradients and test underlying causes. Location Simulated global meta‐community. Methods We constructed a spatially explicit global meta‐community with constant per capita rates of disturbance, speciation and dispersal. No gradient emerged in this neutral base model. Focusing on the oceans as a model system, we added a water temperature gradient of 0–30°C that independently affected rates of community turnover and speciation based on established metabolic scaling laws. We also added a gradient in habitat area that roughly parallels the observed decrease in ocean area from tropical to polar waters. Results Thermal effects on the community turnover rate caused a transient latitudinal gradient that ultimately disappeared. Thermal effects on speciation produced a dynamically stable but relatively weak gradient. Increasing habitat area towards the equator in combination with thermal effects on speciation rate produced a more realistic gradient that emerged from the combined effects of species–area and species–energy theory. Main conclusions This reasonably simple model provides a platform to explore support for processes underpinning large‐scale biodiversity gradients, and the ability of prominent ecological theories, independently or in combination, to capture them.

Marine extinction risk shaped by trait–environment interactions over 500 million years - Emily A. Orzechowski; Rowan Lockwood; Jarrett E. K. Byrnes; Sean C. Anderson; Seth Finnegan; Zoe V. Finkel; Paul G. Harnik; David R. Lindberg; Lee Hsiang Liow; Heike K. Lotze; Craig R. McClain; Jenny L. McGuire; et al. (Global Change Biology, 2015)
Perhaps the most pressing issue in predicting biotic responses to present and future global change is understanding how environmental factors shape the relationship between ecological traits and extinction risk. The fossil record provides millions of years of insight into how extinction selectivity (i.e., differential extinction risk) is shaped by interactions between ecological traits and environmental conditions. Numerous paleontological studies have examined trait‐based extinction selectivity; however, the extent to which these patterns are shaped by environmental conditions is poorly understood due to a lack of quantitative synthesis across studies. We conducted a meta‐analysis of published studies on fossil marine bivalves and gastropods that span 458 million years to uncover how global environmental and geochemical changes covary with trait‐based extinction selectivity. We focused on geographic range size and life habit (i.e., infaunal vs. epifaunal), two of the most important and commonly examined predictors of extinction selectivity. We used geochemical proxies related to global climate, as well as indicators of ocean acidification, to infer average global environmental conditions. Life‐habit selectivity is weakly dependent on environmental conditions, with infaunal species relatively buffered from extinction during warmer climate states. In contrast, the odds of taxa with broad geographic ranges surviving an extinction (>2500 km for genera, >500 km for species) are on average three times greater than narrow‐ranging taxa (estimate of odds ratio: 2.8, 95% confidence interval = 2.3–3.5), regardless of the prevailing global environmental conditions. The environmental independence of geographic range size extinction selectivity emphasizes the critical role of geographic range size in setting conservation priorities.

Integrated assessment models for ecologists: the present and the future - Michael Harfoot; Derek P. Tittensor; Tim Newbold; Greg McInerny; Matthew J. Smith; Jörn P. W. Scharlemann (Global Ecology and Biogeography, 2014)
Aim Human impacts on the biosphere are a matter of urgent and growing concern, with ecologists increasingly being asked to project biodiversity futures. The Intergovernmental Platform on Biodiversity and Ecosystem Services ( IPBES ) is likely to comprehensively assess such projections, yet despite being widely used and potentially critical tools for analysing socio‐environmental futures, integrated assessment models ( IAM s) have received little attention from ecological modellers. We aim to raise awareness and understanding of IAM s among ecologists by describing the structure and composition of IAM s, assessing their utility for biodiversity projections and identifying limitations that hamper greater interaction between scientists using IAMs and those using ecological models. We also hope to inspire more accessible and applicable models by suggesting development needs for IAM s. Methods We conduct a systematic review of four state‐of‐the‐art IAM s, which describes and contrasts key model features and analyses six aspects of IAM s that are of fundamental interest to ecologists. Conclusions IAM s could be valuable for modelling biodiversity futures; however, current IAM s were not developed for this application and challenges remain for ecologists looking to use their outputs. Separating and understanding the differences resulting from IAM formulation and those resulting from specific scenario assumptions is currently problematic, and current IAM s may be unable to accurately represent environmental conditions for both Earth‐system projections and for building robust models of biodiversity because key ecological processes are absent. We suggest that model intercomparisons would identify differences in model dynamics, and detailed studies of how dynamical interactions between components influence behaviour would address why such differences arise. Bio‐economic fisheries models and agriculture pollination models provide starting points for integrating key ecological feedbacks within IAM s. Ultimately, making IAM s more accessible within the multidisciplinary study of global change, drawing on user‐centred research, would enable more resolved, reliable and accurate assessment of how Earth's socio‐ecological system is approaching planetary boundaries.

Global habitat suitability of cold‐water octocorals - Chris Yesson; Michelle L. Taylor; Derek P. Tittensor; Andrew J. Davies; John Guinotte; Amy Baco; Julie Black; Jason M. Hall‐Spencer; Alex D. Rogers (Journal of Biogeography, 2012)
Aim Three‐quarters of Octocorallia species are found in deep waters. These cold‐water octocoral colonies can form a major constituent of structurally complex habitats. The global distribution and the habitat requirements of deep‐sea octocorals are poorly understood given the expense and difficulties of sampling at depth. Habitat suitability models are useful tools to extrapolate distributions and provide an understanding of ecological requirements. Here, we present global habitat suitability models and distribution maps for seven suborders of Octocorallia: Alcyoniina, Calcaxonia, Holaxonia, Scleraxonia, Sessiliflorae, Stolonifera and Subselliflorae. Location Global. Methods We use maximum entropy modelling to predict octocoral distribution using a database of 12,508 geolocated octocoral specimens and 32 environmental grids resampled to 30 arc‐second (approximately 1 km 2 ) resolution. Additionally, a meta‐analysis determined habitat preferences and niche overlap between the different suborders of octocorals. Results Suborder Sessiliflorae had the widest potential habitat range, but all records for all suborders implied a habitat preference for continental shelves and margins, particularly the North and West Atlantic and Western Pacific Rim. Temperature, salinity, broad scale slope, productivity, oxygen and calcite saturation state were identified as important factors for determining habitat suitability. Less than 3% of octocoral records were found in waters undersaturated for calcite, but this result is affected by a shallow‐water sampling bias. Main conclusions The logistical difficulties, expense and vast areas associated with deep‐sea sampling leads to a gap in the knowledge of faunal distributions that is difficult to fill without predictive modelling. Global distribution estimates are presented, highlighting many suitable areas which have yet to be studied. We suggest that approximately 17% of oceans are suitable for at least one suborder but 3.5% may be suitable for all seven. This is the first global habitat suitability modelling study on the distribution of octocorals and forms a useful resource for researchers, managers and conservationists.

Elevated species diversity in abyssal gastropods off Newfoundland: the potential role of food supply - Carol T. Stuart; Michael A. Rex; Derek P. Tittensor; Craig R. Smith (Marine Biodiversity, 2011)

Acute effects of removing large fish from a near-pristine coral reef - Douglas J. McCauley; Fiorenza Micheli; Hillary S. Young; Derek P. Tittensor; Daniel R. Brumbaugh; Elizabeth M. P. Madin; Katherine E. Holmes; Jennifer E. Smith; Heike K. Lotze; Paul A. DeSalles; Suzanne N. Arnold; Boris Worm (Marine Biology, 2010)

Seamounts as refugia from ocean acidification for cold‐water stony corals - Derek P. Tittensor; Amy R. Baco; Jason M. Hall‐Spencer; James C. Orr; Alex D. Rogers (Marine Ecology, 2010)
Cold‐water stony corals create habitat for a diverse range of deep‐water species but are thought to be threatened by ocean acidification due to oceanic uptake of anthropogenic CO 2 . Knowledge of the severity of this threat is hampered by our limited understanding of the distribution and habitat requirements of these corals. Here we estimate the global acidification threat to these organisms using a global database of cold‐water stony coral records and a species distribution modelling approach. We parameterised the models using present‐day environmental data, and then replaced these data with future projections of ocean chemistry from the year 2099. We found suitable coral habitat to be very heterogeneously distributed, being concentrated in the northern North Atlantic and around New Zealand. Projected changes in ocean chemistry induced a pronounced reduction in habitat suitability in the North Atlantic, and a low‐to‐moderate impact elsewhere under both the IPCC IS92a and S650 scenarios. Seamount summits are impacted by these changes, but consistently provide more suitable habitat than the surrounding seafloor, with around 98% of seamount summits having higher suitability in both future scenarios; this is because they lie in shallower waters with a higher aragonite saturation state. These results suggest that anthropogenic‐induced changes in ocean chemistry are likely to severely impact cold‐water stony coral habitat in the deep‐sea of the North Atlantic, and that impacts will be less severe elsewhere. We predict that coral communities on the summits and upper slopes of seamounts will be less susceptible to ocean acidification during this century than those on the surrounding seafloor, and thus that seamounts may serve as temporary refugia.

Environmental drivers of ophiuroid species richness on seamounts - Timothy D. O’Hara; Derek P. Tittensor (Marine Ecology, 2010)
Benthic communities on seamounts are frequently characterised as being species rich, yet there is considerable variation in observed species richness. Although large‐scale patterns of species richness have been described from many marine and terrestrial habitats, their environmental drivers often remain poorly understood. We compared species richness of ophiuroids (brittle‐stars) on 60 seamounts throughout the South West Pacific Ocean, and used an information‐theoretic approach and generalized linear models to determine the relative importance of predictor variables. Due to high correlation among many environmental variables, we used a reduced set of predictors in an a priori model framework. Temperature was the only environmental predictor of any importance in these models over the bathymetric range of the study. Post‐hoc analyses of other potential environmental predictor variables showed that depth, calcite saturation state, temperature range, modelled current velocity and latitude all had some predictive value, but were also highly correlated with temperature or other environmental variables included in the a priori model. Longitude, large‐area species richness, habitat suitability for stony corals, and modelled POC flux did not have high predictive value. We hypothesise that temperature affects richness by constraining species distributions; in particular fewer species can tolerate the conditions on relatively warm shallow seamount summits.

An index to assess the risk to stony corals from bottom trawling on seamounts - Malcolm R. Clark; Derek P. Tittensor (Marine Ecology, 2010)
Stony (scleractinian) corals are common on seamounts and can form extensive reef‐like structures which in turn provide important habitat for associated species. Aggregations of fish also occur on seamounts, which in recent decades have become the target of commercial bottom trawl fisheries that have damaging impacts on benthic communities. Such fisheries occur throughout the world’s oceans, and the majority are located on seamounts about which little is known of their biodiversity or likely fisheries impact. Here we develop an index of risk for stony corals on seamount summits. The index combines a metric of vulnerability measured by the coincidence of seamount summits, target fish ranges and likelihood of coral presence with an assessment of likely fisheries impact derived from a fishing intensity effects study and fishing effort‐catch data. We provide spatial maps depicting the locations of vulnerable seamount features, and those at particular risk to bottom trawling. Application of the risk index may help to provide guidance to fisheries or environmental managers faced with balancing fisheries management and habitat conservation.

Predicting global habitat suitability for stony corals on seamounts - Derek P. Tittensor; Amy R. Baco; Paul E. Brewin; Malcolm R. Clark; Mireille Consalvey; Jason Hall‐Spencer; Ashley A. Rowden; Thomas Schlacher; Karen I. Stocks; Alex D. Rogers (Journal of Biogeography, 2009)
Aim Globally, species distribution patterns in the deep sea are poorly resolved, with spatial coverage being sparse for most taxa and true absence data missing. Increasing human impacts on deep‐sea ecosystems mean that reaching a better understanding of such patterns is becoming more urgent. Cold‐water stony corals (Order Scleractinia) form structurally complex habitats (dense thickets or reefs) that can support a diversity of other associated fauna. Despite their widely accepted ecological importance, records of scleractinian corals on seamounts are patchy and simply not available for most of the global ocean. The objective of this paper is to model the global distribution of suitable habitat for stony corals on seamounts. Location Seamounts worldwide. Methods We compiled a database containing all accessible records of scleractinian corals on seamounts. Two modelling approaches developed for presence‐only data were used to predict global habitat suitability for seamount scleractinians: maximum entropy modelling (Maxent) and environmental niche factor analysis (ENFA). We generated habitat‐suitability maps and used a cross‐validation process with a threshold‐independent metric to evaluate the performance of the models. Results Both models performed well in cross‐validation, although the Maxent method consistently outperformed ENFA. Highly suitable habitat for seamount stony corals was predicted to occur at most modelled depths in the North Atlantic, and in a circumglobal strip in the Southern Hemisphere between 20° and 50° S and shallower than around 1500 m. Seamount summits in most other regions appeared much less likely to provide suitable habitat, except for small near‐surface patches. The patterns of habitat suitability largely reflect current biogeographical knowledge. Environmental variables positively associated with high predicted habitat suitability included the aragonite saturation state, and oxygen saturation and concentration. By contrast, low levels of dissolved inorganic carbon, nitrate, phosphate and silicate were associated with high predicted suitability. High correlation among variables made assessing individual drivers difficult. Main conclusions Our models predict environmental conditions likely to play a role in determining large‐scale scleractinian coral distributions on seamounts, and provide a baseline scenario on a global scale. These results present a first‐order hypothesis that can be tested by further sampling. Given the high vulnerability of cold‐water corals to human impacts, such predictions are crucial tools in developing worldwide conservation and management strategies for seamount ecosystems.

Human impacts on the species–area relationship in reef fish assemblages - Derek P. Tittensor; Fiorenza Micheli; Magnus Nyström; Boris Worm (Ecology Letters, 2007)
The relationship between species richness and area is one of the oldest, most recognized patterns in ecology. Here we provide empirical evidence for strong impacts of fisheries exploitation on the slope of the species–area relationship (SAR). Using comparative field surveys of fish on protected and exploited reefs in three oceans and the Mediterranean Sea, we show that exploitation consistently depresses the slope of the SAR for both power‐law and exponential models. The magnitude of change appears to be proportional to fishing intensity. Results are independent of taxonomic resolution and robust across coral and rocky reefs, sampling protocols and statistical methods. Changes in species richness, relative abundance and patch occupancy all appear to contribute to this pattern. We conclude that exploitation pressure impacts the fundamental scaling of biodiversity as well as the species richness and spatial distribution patterns of reef fish. We propose that species–area curves can be sensitive indicators of community‐level changes in biodiversity, and may be useful in quantifying the human imprint on reef biodiversity, and potentially elsewhere.